The Efficacy of Topical Cosmetic Containing Alpha‐Arbutin 5% and Kojic Acid 2% Compared With Triple Combination Cream for the Treatment of Melasma: A Split‐Face, Evaluator‐Blinded Randomized Pilot Study - Tantanasrigul, Pimpa; Sripha, Apinya; Chongmelaxme, Bunchai (Journal of cosmetic dermatology, 2025)
ABSTRACT Background While the gold standard treatment for melasma is triple combination cream (TCC), arbutin and kojic acid demonstrate their benefits and may be used as an alternative. Aims To investigate the efficacy of cream containing alpha‐arbutin 5% and kojic acid 2% (AAK) compared with TCC for melasma treatment. Patients/Methods A split‐faced, randomized study was conducted among 30 participants with melasma, and all were randomized to receive AAK or TCC on each side of their face for 12‐week along with 4‐week follow‐up period. The melanin index (MI), modified Melasma Area Severity Index (mMASI), and physician global assessment (PGA) scores were used to measure the effectiveness of interventions. Recurrence of melasma after treatment discontinuation was evaluated by MI and mMASI. Patient satisfactions and adverse effects were also evaluated. In the analysis, the mean difference (MD) was used for MI and mMASI, while Wilcoxon signed‐rank test was for the PGA scores, adverse effects, and patient satisfaction. Results The MD of MI and mMASI scores were not different between groups (mMASI [p = 0.344] and MI [p = 0.268]). The PGA scores only showed improvement on the TCC‐treated side (p = 0.032). Compared to the AKK group, the subjects with TCC showed higher severity of recurrence (MI [p = 0.004] and mMASI [p = 0.045]). No difference in patient satisfaction score between the groups, but erythema and stinging were higher in the TCC group. Conclusions The AAK cream appeared to be effective for melasma treatment, highlighting a lower recurrent rate and fewer adverse events than standard therapy. Trial Registration: thaiclinicaltrials.org: TCTR20230124004